2021
DOI: 10.1785/0220200407
|View full text |Cite
|
Sign up to set email alerts
|

The Portuguese National Seismic Network—Products and Services

Abstract: Portugal, located in the southwest region of the Eurasian plate, has been affected by several destructive earthquakes throughout its history, the most well-known being the 1755 Great Lisbon earthquake. The seismicity of the territory, both in the mainland and in the Azores and Madeira islands, has prompted the continuous development of seismic monitoring, from the first known macroseismic inquiry, following the 1755 Great Lisbon earthquake, to the current state-of-the-art seismic network. Once scattered in sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Data was recorded continuously at 40, 50, 80 and 100 samples per second. More detailed information on the permanent networks and on the WILAS temporary network (Dias et al 2010) can be found in Carrilho et al (2021) and Custódio et al (2014). The DOCTAR deployment is described in Matos et al (2018).…”
Section: Data P Ro C E S S I N Gmentioning
confidence: 99%
“…Data was recorded continuously at 40, 50, 80 and 100 samples per second. More detailed information on the permanent networks and on the WILAS temporary network (Dias et al 2010) can be found in Carrilho et al (2021) and Custódio et al (2014). The DOCTAR deployment is described in Matos et al (2018).…”
Section: Data P Ro C E S S I N Gmentioning
confidence: 99%
“…The two EGIM to be installed in these observatories have already been submitted to factory acceptance tests and sea acceptance tests during 2021 being the deployment scheduled for mid 2022. Underwater acoustics, that can also provide cost-efficient information for the follow up of marine mammal population dynamics, the characterization of fish reproduction changes, the understanding of adverse meteo-oceanographic conditions, can also lead to the identification of low-energy seismic events that will be used to support the operation and development of the tsunami and seismic early warning systems, under the responsibility of IPMA (Carrilho et al, 2021). Focus will be given to a better understanding of seismic and geological risk sources.…”
Section: The Need Of Ocean Observatories and Laboratories To Support ...mentioning
confidence: 99%
“…IPMA (Instituto Português do Mar e da Atmosfera) is the Portuguese Agency responsible for earthquake and tsunami monitoring and it has the responsibility to inform authorities as fast as possible on occurring earthquakes and possible tsunamis. For this purpose, IPMA is collecting seismic data from a dense network, exclusively based on land stations, many of them available through international cooperation (Figure 3) (Carrilho et al, 2021). Figure 3 also shows the FIGURE 2 | Sketch location of the submarine telecom cables in operation at the Azores archipelago (yellow and red lines) overlaying the shaded bathymetry map (Smith and Sandwell, 1997).…”
Section: Earthquake and Tsunami Monitoringmentioning
confidence: 99%